Survival after diagnosis of hypertension in cats attending primary care practice in the United Kingdom - Conroy, M; Chang, Y; Brodbelt, D; Elliott, J (Wiley, 2018)
Background Hypertension is common in older cats. There is limited evidence for predictors of survival after diagnosis. Hypothesis/Objectives Investigate blood pressure assessment (BPA) and hypertension diagnosis in cats attending UK primary care practices (PCPs) and factors that influence survival. Animals Cats (347 889) attending 244 UK PCPs enrolled in the VetCompass program between January 1, 2012, and December 31, 2013. Cats identified as hypertensive (282) were included in descriptive and survival analyses. Methods All electronic patient records (EPRs) were searched to identify cats that potentially had received BPA. EPRs were read in detail to identify those that had BPA. The proportion that received BPA was evaluated using a stratified analysis and the incidence of hypertension estimated. A retrospective cohort study was used to investigate survival after diagnosis (Cox proportional hazard model). Results Estimated incidence risk was 19.5% (95% confidence interval [CI], 17.5‐21.6) from the estimated 1.34% (1.30%‐1.38%) of cats that received BPA. Few cats had BPA more than once after diagnosis (median, 1; interquartile range [IQR], 0‐3), with only 9.9% of diagnosed hypertensive cats having urine protein:creatinine ratio determined. Cats diagnosed as a result of monitoring of pre‐existing disease had improved survival (hazard ratio [HR], 0.58; 95% CI, 0.37‐0.89; P = .01) compared to cats diagnosed after clinical signs were recognized. Cats that had an amlodipine dose change had improved survival (HR, 0.56; 95% CI, 0.36‐0.87; P = .01) compared to those with no dose change. Conclusions and clinical importance These data suggest improved blood pressure monitoring in clinical practice may decrease the morbidity associated with hypertension.